Effect of Motivational Interviewing and Exercise on Chronic Low Back Pain: A Systematic Review and Meta‐ Analysis - Opeyemi Idowu (Musculoskeletal Care, 2025)
Background: The prevalence of chronic low back pain (CLBP) and its concomitant cost implications have continued to rise across the globe. Currently, there is no effective treatment for CLBP that leads to long‐term improvement. Hence, there is growing recognition of the need for behaviour techniques including motivational interviewing (MI) to address CLBP. Objective: To determine the effect of MI and exercise on pain in individuals with CLBP. Method: We searched for trials in seven databases from inception to April 2024. Trials were included if MI was used alone or in addition to an exercise programme for improving CLBP in adults aged (≥ 18 years). Results: From 3062 records retrieved, we included three randomized controlled trials (RCTs). Only one study was rated as having a low risk of bias. There is no evidence to support the benefit of MI and exercise on improving pain (SMD‐0.23, 95% CI‐ 0.55 to 0.09, I2 = 0%, p = 0.16), disability (MD‐1.80, 95% CI‐4.55 to 0.94, I2 = 85%, p = 0.20) and physical functioning (SMD 0.00, 95% CI‐1.31 to 1.32, I2 = 93%, p = 0.99). Conclusion: There is insufficient evidence to support the effect of MI and exercise on pain in individuals with CLBP. More large‐scale RCTs are needed in evaluating the effectiveness of MI and exercise in individuals with CLBP